Effects of aging and cardiovascular disease risk factors on the expression of sirtuins in the human corpus cavernosum - Freitas, M. (2015)
Introduction. Sirtuin (SIRT) 1 was recently identified in human corpus cavernosum (CC). We hypothesized that other sirtuins could also be expressed in the CC. Expression of these enzymes in tissues is affected by aging, the main independent risk factor for erectile dysfunction besides other cardiovascular disease risk factors (CVDRF), such as diabetes or obesity. Aim. The aim of this study was to characterize the expression of SIRT1-3 and SIRT5-7 in human CC relatively to age and CVDRF. Methods. Samples of CC collected from patients submitted to programmed surgeries or organ donors were divided in three groups according to age and presence of CVDRF. Expression of SIRT1-3 and SIRT5-7 mRNAs was assessed by real-time polymerase chain reaction. Cellular localization and semi-quantification of sirtuins proteins were performed by immunofluorescence and Western blotting (WB), respectively. Nuclear factor kappa B (NFkB)-p65, inducible (iNOS) and endothelial nitric oxide synthase (eNOS) levels were also assayed by WB. Main Outcome Measures. The main outcome measure was to characterize the expression of SIRT1-3 and SIRT5-7 in human CC. Results. SIRT1-3 and SIRT5-7 mRNAs were detected in all individuals, without statistical differences among groups, excepting SIRT7 that decreased four times in aged groups relatively to young (P = 0.013). WB analysis demonstrated that aged individuals with CVDRF presented higher levels of SIRT7 protein relatively to young (P = 0.0495) and lower levels of SIRT3 protein relatively to healthy aged (P = 0.0077). Expression of NFkB-p65 and iNOS were higher in aged than in young individuals (P = 0.0185; P = 0.004, respectively). No differences in other sirtuins or total eNOS were seen among groups although phospho eNOS Ser(1177) levels decreased in groups of aged men relatively to young (P = 0.0043; P = 0.0099). Conclusions. Our results demonstrate for the first time expression of SIRT2-3 and SIRT5-7 in the human CC. Aged individuals with CVDRF presented an increase in SIRT7 protein levels and a decrease in mitochondrial SIRT3. This finding suggests that CVDRF induces the loss of antioxidant defense mechanisms leading to endothelial injury.